2021
DOI: 10.3389/fphar.2020.596525
|View full text |Cite
|
Sign up to set email alerts
|

The Traditional Chinese Medicine Fuyou Formula Alleviates Precocious Puberty by Inhibiting GPR54/GnRH in the Hypothalamus

Abstract: The purpose of this study was to explore the effect of the traditional Chinese medicine Fuyou formula on precocious puberty (PP). The Fy formula may exert an effect in female rats with PP and GT-7 cells through the GPR54/GnRH signaling pathway. To confirm the effect of the Fy formula on PP through the GPR54/GnRH signaling pathway, we first treated GT1-7 cells with the Fy formula and observed changes in the expression of related genes and proteins and in GnRH secretion. Then, we randomly divided young female Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…The PP rat model has been used in several previous studies to evaluate the effects of herbal mixtures from Oriental medicine. Recently, Bai et al studied the effect of the Fuyou formula, containing Anemarrhenae rhizome and Rehmanniae radix , on GT1-7 cells and danazol-induced PP rats [ 26 ]. The results showed that the Fuyou formula alleviated the symptoms in rats with PP and downregulated the GPR54/GnRH signaling pathway in GT1-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The PP rat model has been used in several previous studies to evaluate the effects of herbal mixtures from Oriental medicine. Recently, Bai et al studied the effect of the Fuyou formula, containing Anemarrhenae rhizome and Rehmanniae radix , on GT1-7 cells and danazol-induced PP rats [ 26 ]. The results showed that the Fuyou formula alleviated the symptoms in rats with PP and downregulated the GPR54/GnRH signaling pathway in GT1-7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the treatment with Fy formula can result in a significantly reduction in the level of E2, LH and FSH in Sprague-Dawley rats ( Guo et al, 2021b ). Furthermore, it has been illustrated that the Fy formula is able to downregulate the expression of Kiss1, GPR54, and GnRH in female rats ( Bai et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been showed that the Fy formula induces downregulation of the mRNA expression of kiss1, GPR54, and GnRH in female rats ( Bai et al, 2020 ). A previous integrated pharmacological study on the mechanism of Fy formula in treating PP demonstrated that it can effectively reduce the levels of FSH, LH, and E 2 in Sprague-Dawley rats ( Guo et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that GnRH release may be related to PKC and phosphorylated ERK1/2, as phosphorylation of these proteins is considered the main cellar signaling event in the activation of the GPR54-GnRH pathway (32,33). To further explore the potential molecular regulatory mechanism of gut microbiota-derived SCFAs of the GPR54-GnRH signaling pathway in the hypothalamus, we measured the protein levels of GPR54, PKC, and ERK1/2 in the hypothalamus (Figure 8A) and examined the secretion of GnRH in the hypothalamus between the HF group and the SCFAs supplement groups.…”
Section: Scfas Regulate Hypothalamic Gnrh Release Through the Gpr54-p...mentioning
confidence: 99%